Dynamics of Technology Roadmapping (TRM) implementation - Nathasit Gerdsri (2018)
To achieve a sustainable competitive advantage, organizations apply Technology Roadmapping (TRM) as an effective tool to link technology into business strategies. The overall objective for today's business is to strengthen their core competencies and their adaptability to business dynamics. Critical factors to the successful initiation and implementation of a roadmap development are People, Processes and Data. This paper focuses on People factor by emphasizing the needs to understand how the roles and responsibilities of key player involved in the TRM process evolve over time in order to match with the dynamics of TRM implementation. © 2007 PICMET.